1983
DOI: 10.1172/jci111000
|View full text |Cite
|
Sign up to set email alerts
|

Defective binding of macrophages to bone in rodent osteomalacia and vitamin D deficiency. In vitro evidence for a cellular defect and altered saccharides in the bone matrix.

Abstract: A B S T R A C T In the osteomalacic as well as normal skeleton, few osteoclasts are associated with osteoidcovered bone surfaces. The reason for this particular cellular deficit is not clear, but may relate to the inability of osteoclasts and/or osteoclast precursors (monocyte-macrophages) to attach to immature, unmineralized bone matrix, a step apparently essential for normal resorptive activity and osteoclast differentiation. In this study, we have examined cell-bone binding using macrophages (MO) and bone i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

1985
1985
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(4 citation statements)
references
References 22 publications
1
3
0
Order By: Relevance
“…The phagocytic capacity also showed an increase at this time, but at the other two doses of vitamin tested. These results also agree with some in vitro studies carried out in mammals, including humans, in which vD 3 enhanced chemotaxis, phagocytosis and cytotoxic functions [47][48][49][50][51][52].…”
Section: Discussionsupporting
confidence: 91%
“…The phagocytic capacity also showed an increase at this time, but at the other two doses of vitamin tested. These results also agree with some in vitro studies carried out in mammals, including humans, in which vD 3 enhanced chemotaxis, phagocytosis and cytotoxic functions [47][48][49][50][51][52].…”
Section: Discussionsupporting
confidence: 91%
“…It has been reported previously, from studies in vitro, that macrophages, which are osteoclast precursors, bind poorly to demineralized bone. (36) However, other studies have reported that osteoclasts bind, in vitro and in vivo, to both demineralized and mineralized bone, (37) and although they will not form ruffled borders (38) and secrete acid, they can continue to release degradative enzymes and resorb bone matrix; that is, they adhere and remain at least partly functional. (37) In our studies, the reductions in osteoclasts appeared to be similar both on the nonmineralized and mineralized bone surfaces of these models when they were osteomalacic on a normal diet.…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin D is a steroid hormone that participates in broad physiological actions [15] , [16] , [17] , [18] . Abnormal vitamin D-related regulations have resulted in skeletal diseases such as rickets and osteomalacia [19] , [20] , catabolic bone remodeling [20] , [21] , [22] , autoimmune diseases [23] , and increased susceptibility to infectious diseases [24] . However, the role of vitamin D in the establishment of osseointegration has not been addressed.…”
Section: Introductionmentioning
confidence: 99%